O problema de roteamento e programação de navios com coleta e entrega na indústria de petróleo : modelagem e métodos de solução exatos - Furtado, Maria Gabriela Stevanato (Universidade Federal de São Carlos, 2016)
The object of this study is the routing and scheduling problem of vessels with pickup and delivery and time windows in the oil industry. A case study was performed in a Brazilian oil industry that produces crude oil in o shore platforms, that is, located in the ocean, and transports to the terminals located in the Brazilian coast. Then, it was proposed a mixed integer model to represent the problem adequately and for this, a detailed analysis of the real problem in order to know all its characteristics and consider some simplifying assumptions. Therefore, to the pickup and delivery problem with time windows present in the literature were aggregated other speci c restrictions of the case study, for example, multiple depots, ship mooring restrictions, exible draft and dynamic positioning. Besides that, the eet is heterogeneous related to capacity, LOA (length overall), dynamic positioning and velocity. In practice, in general there are no identical vessels. This problem can be represented as a combinatorial optimization model, which belongs to the NP-hard class and its solution is a challenging in practice depending on the size of the real problems. Then, were proposed several exact branch-and-cut methods based on models with 2 and 3-index variables for routing problems with pickup and delivery and time windows to solve speci cally the Brazilian oil industry problem. Finally, we proposed a branch-and-price method, which includes all characteristics of the problem in oil industry. In summary, the main contributions of this thesis are related to the study and modeling of this problem in practice, and the proposal and development of exact solution methods to solve it, based on branch-and-cut and branch-and-price. The performance of the mathematical model in optimization software and the exact methods were veri ed using a real data set provided by the company. Results show that these approaches may be e ective to solve problems of moderate size in real situations.
Keywords: Roteamento e programação de navios; Problemas de coleta e entrega; Indústria petrolífera; Métodos exatos; Método branch-and-cut; Método branch-and-price; Routing and scheduling of vessels; Pickup and delivery problem; Oil industry; Exact methods; Branch-and-cut method; Branch-and-price method; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL